General Difference Schemes with Intrinsic Parallelism for Semilinear Parabolic Systems of Divergence Type (Journal of Computational Mathematics, 1999)
In this paper the general finite difference schemes with intrinsic parallelism for the boundary value problem of the semilinear parabolic system of divergence type with bounded coefficients are constructed, and the existence and uniqueness of the difference solution for the general schemes are proved. And the convergence of the solutions of the difference schemes to the generalized solution of the original boundary value problem of the semilinear parabolic system is obtained. The multi-dimensional problems are also studied.
Keywords: Difference scheme; Intrinsic parallelism; Semilinear parabolic system; Convergence.